2010
DOI: 10.1186/1471-244x-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Ego defense mechanisms in Pakistani medical students: a cross sectional analysis

Abstract: BackgroundEgo defense mechanisms (or factors), defined by Freud as unconscious resources used by the ego to reduce conflict between the id and superego, are a reflection of how an individual deals with conflict and stress. This study assesses the prevalence of various ego defense mechanisms employed by medical students of Karachi, which is a group with higher stress levels than the general population.MethodsA questionnaire based cross-sectional study was conducted on 682 students from five major medical colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
5
18
2
Order By: Relevance
“…It has demonstrated good construct and content validity by discriminating between different psychiatric populations in various studies and adequate reliability statistics with test-retest reliability (.66) and high inter-item correlations (.78) [ 13 , 34 - 35 ]. It is one of the most extensively used self-report measures to assess ego defense mechanisms in various countries, such as Pakistan, Iran, Finland, Canada, Brazil, Japan, and Denmark, both in psychiatric patients, medical students, and the general public of varying ages [ 27 - 28 , 36 - 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has demonstrated good construct and content validity by discriminating between different psychiatric populations in various studies and adequate reliability statistics with test-retest reliability (.66) and high inter-item correlations (.78) [ 13 , 34 - 35 ]. It is one of the most extensively used self-report measures to assess ego defense mechanisms in various countries, such as Pakistan, Iran, Finland, Canada, Brazil, Japan, and Denmark, both in psychiatric patients, medical students, and the general public of varying ages [ 27 - 28 , 36 - 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, only one study has investigated the defense mechanisms of medical students in Pakistan according to which the most commonly employed ego defenses by medical students were rationalization, anticipation, and undoing while the defenses of devaluation, denial, and displacement were least common [ 27 ]. However, the study by Parekh, et al was limited to the prevalence of defense mechanisms and did not assess associations of ego defenses with anxiety, depression, or psychosocial functioning in medical students [ 27 ]. In a similar study using the Defense Style Questionnaire-40 (DSQ-40), La Cour reported a higher use of pseudo-altruism, dissociation, denial, sublimation, and suppression in medical students than high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, defense mechanisms have been investigated in relation to different behaviors such as depression, anxiety, normal people, educational advance, etc. by different researchers during recent years (6,17,19,20,34,35). In relation to the research variables, the results of covariance analysis of experimental and control groups determined that all variables ex-4…”
Section: Discussionmentioning
confidence: 99%
“…projection) have been found to be associated with negative health indices such as personality disorders, depression, and drug use [13]. A greater use of neurotic and immature defenses is reported in mental disorders, such as panic disorder, obsessivecompulsive disorder, social phobia and major depression [14] while immature defense mechanisms were less commonly employed than neurotic and mature mechanisms, among medical students [15].…”
Section: Introductionmentioning
confidence: 99%